2015
DOI: 10.1177/0884533615622536
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Guide for the Use of Metabolic Carts

Abstract: Critically ill patients often require nutrition support, but accurately determining energy needs in these patients is difficult. Energy expenditure is affected by patient characteristics such as weight, height, age, and sex but is also influenced by factors such as body temperature, nutrition support, sepsis, sedation, and therapies. Using predictive equations to estimate energy needs is known to be inaccurate. Therefore, indirect calorimetry measurement is considered the gold standard to evaluate energy needs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0
6

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 89 publications
0
23
0
6
Order By: Relevance
“…11 Poor reimbursement by insurance for tests performed has also been considered a barrier to using IC. 8 As a result, predictive equations have been recommended as surrogates for IC, despite accuracies which range from 0% to 77%. 15 Unfortunately, those healthcare professionals who do not receive a strong education in nutrition or are not familiar with critical care medicine do not recognize these formulae were created based on healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…11 Poor reimbursement by insurance for tests performed has also been considered a barrier to using IC. 8 As a result, predictive equations have been recommended as surrogates for IC, despite accuracies which range from 0% to 77%. 15 Unfortunately, those healthcare professionals who do not receive a strong education in nutrition or are not familiar with critical care medicine do not recognize these formulae were created based on healthy individuals.…”
Section: Discussionmentioning
confidence: 99%
“…These patients cannot undergo IC as these variables may cause inaccuracies in the measurements. 8 The clinical information used in this study originated from patients' electronic medical record (EMR) and consisted of age (years), gender (female, male), height, weight, body mass index (BMI), minute ventilation, temperature (in °C), and heart rate (beats per minute). The patient's height used in the study was either recumbent length or reported height.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…9 However, in this study, IC was performed in patients during RRT and IC guidelines contraindicate this moment for the measurement of EE, due to possible interferences of the dialysis procedure in gas exchange, which would lead to errors in the measurement of EE using IC. 5,10,11 The present study aims to evaluate the daily variability of REE measured by IC in patients with AKI and dialytic indication and to identify the clinical variables associated with REE.…”
Section: Introductionmentioning
confidence: 99%